Caso radiológico: tuberculose pleural - Almeida, A. (2010)
The authors report a case of pleural tuberculosis in a 15-year-old boy submitted to screening after his father was diagnosed with the disease. This patient had constitutional symptoms in the last two months (such as significant weight loss, fatigue, anorexia and night sweats) but no respiratory complains. The thoracic X-ray complemented by a CT scan revealed pleural effusion with minimal pulmonary changes. Pleural fluid analysis and pleural biopsy confirmed the diagnosis of pleural tuberculosis. This case highlights the non specific clinic and imaging findings in tuberculosis and the need for a high index of suspicion to reach the diagnosis.